Effect of PRECEDE-PROCEED-Model-Based Health Education on the Life Quality and 5-HTT Gene Expression of Patients with Gastric Cancer after Surgery - Wang, Guifang; Jiang, Xueyan (Cellular and Molecular Biology, 2022)
This study aimed to investigate the effect of PRECEDE-PROCEED-Model-based health education on the life quality of patients with gastric cancer after surgery. Also, the effect of this model was evaluated on 5-HTT gene expression as a gene related to depression. For this purpose, a total of 32 gastric cancer patients who were hospitalized in this hospital between March 2019 and September 2020 were enrolled in this study after surgery and, according to the time of admission, were divided into the control group and observation group, with 16 patients in each group. Patients in the control group were nursed regularly, while those in the observation group, in addition to the regular nursing, would receive the PRECEDE-PROCEED-Model-based health education. Post-surgery life quality of patients in two groups was compared from the following aspects: Rehabilitation process, pain assessment, rate of complications and The Short-Form (SF-36) Health Survey. The expression of the 5-HTT gene was performed by the Real-time qPCR technique. The results of this study showed that after surgery, the extubation time and the time of hospital discharge of patients in the observation group were all earlier than those in the control group, while the score of pain assessment and rate of complication was much lower in the observation group, and the SF-36 score of patients was much higher (all P < 0.05). The results of 5-HTT gene expression showed that there was no significant difference between the control and observation groups before the intervention. But one month after the intervention, gene expression in the observation group was significantly reduced compared to the control group (p <0.01). This significant decrease was also seen two months after the intervention (p <0.05). As mentioned before, the expression of the 5-HTT gene increases during the depression, therefore improvement of the patient’s condition and quality of life decreased the expression of this gene. Hence, PRECEDE-PROCEED-Model-Based Health Education plays an influential role in reducing the expression of this gene. However, the passage of time has not been ineffective in lowering 5-HTT expression. In general, PRECEDE-PROCEED-Model-based health education could help patients establish a good system of health knowledge, which could encourage the patients to avoid the negative mood, optimize the rehabilitation process, improve the post-surgery rehabilitation and, finally, ameliorate the life quality of patients after surgery.